Electrolytic Macrocyclizations: Scalable Synthesis of a Diazonamide‐Based Drug Development Candidate1. (26th February 2015) - Ding, Hui; DeRoy, Patrick L.; Perreault, Christian; Larivée, Alexandre; Siddiqui, Arshad; Caldwell, Charles G.; Harran, Susan; Harran, Patrick G.
Abstract An electrochemical method to synthesize the core macrolactam of diazonamides is described. Large ring‐forming dehydrogenation is initiated by anodic oxidation at a graphite surface. The reaction requires no tailoring of the substrate and occurs at ambient temperature in aqueous DMF in an undivided cell open to air. This unique chemistry has enabled a concise, scalable preparation of DZ‐2384; a refined analog of diazonamide A slated for clinical development as a cancer therapeutic.